MYTHS AND ORNAMENTATION OF BONDA WOMEN : A CONTINUITY AND CHANGE - Vardhan, V. Ashok (IJRDO - Journal of Social Science and Humanities Research, 2020)
The Bondos / Bondas are habituated to live in the forest at a high attitude of 3,000 feet. In Khairput block of Malkangiri district, they concentrated in the north-west of Machakund River in the Malkangiri district. The Bondo / Bonda women are known for wearing the multiple colors of beads from neck to naval to cover their semi-naked body. The mini skirt (rinda or nadi) is home-woven to proclaim the elf identity. Their attire is symbol of sacrifice and continuity to shield their cultural identity. They are the torch bearers of their community and continuing the rich traditions. The characteristic of semi –nakedness is nothing but genesis of their existence and social status too. In this scenario an ethnographic study was conducted on their ornamentation with special emphasis on beads. The present paper speaks about various myths regarding their semi-nakedness’ and pattern of ornamentation. During the study different age groups of women were considered in 12 villages to understand the usage of ornaments, number of color bead chains they wear and the reasons behind.